Enhancing Economic Reforms through Social Development : Brazil State Pension Systems Reform LIL - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
Resolving the pension crisis in Brazil has been neither straightforward nor technically easy. The World Bank provided technical assistance via diagnostic tools that assessed the impacts of current pensions at the state level. The analysis identified likely impacts various pension reform models might have on different social groups, including the poor. The project was realistic in scope. It was intended only to equip the states technically to address pension reform and to assist in setting up stakeholder discussion groups to openly examine and debate the merits of various pension reform proposals. The government allowed the testing of these diagnostic tools on the social security system. In the end, such technical assistance could achieve only part of the reform. The critical component was building internal government support for constitutional reforms of the pension system. This Note summarizes how the State Pensions system Reform LIL Project created the capacity for learning, trust, and reform.